Tropic Responses of Phycomyces Sporangiophores to Gravitational and Centrifugal Stimuli - Dennison, David S. (The Rockefeller University Press, 1961)
A low-speed centrifuge was used to study the tropic responses of Phycomyces sporangiophores in darkness to the stimulus of combined gravitational and centrifugal forces. If this stimulus is constant the response is a relatively slow tropic reaction, which persists for up to 12 hours. The response is accelerated by increasing the magnitude of the gravitational-centrifugal force. A wholly different tropic response, the transient response, is elicited by an abrupt change in the gravitational-centrifugal stimulus. The transient response has a duration of only about 6 min. but is characterized by a high bending speed (about 5°/min.). An analysis of the distribution of the transient response along the growing zone shows that the active phase of the response has a distribution similar to that of the light sensitivity for the light-growth and phototropic responses. Experiments in which sporangiophores are centrifuged in an inert dense fluid indicate that the sensory mechanism of the transient response is closely related to the physical deformation of the growing zone caused by the action of the gravitational-centrifugal force on the sporangiophore as a whole. However, the response to a steady gravitational-centrifugal force is most likely not connected with this deformation, but is probably triggered by the shifting of regions or particles of differing density relative to one another inside the cell.